(untitled) (GAIMS Journal of Medical Sciences, 2023)
Abruptio placenta can lead to rapid separation of the placenta and result in fetal demise. Secondary to abruption, Disseminated Intravascular Coagulation (DIC) can occur due to inappropriate activation of the coagulation and fibrinolytic system. Once DIC develops, early recognition, specific treatment and repeated tests with aggressive correction of coagulation and electrolyte imbalance along with avoidance of hypothermia and metabolic acidosis help in preventing multi organ failure and mortality.